Pengaruh Pasta Ekstrak Daun Sukun (ArtocarpusAltilis) terhadap Perubahan Sel Fibroblas dan Jaringan Kolagen pada Periodontitis - Irma H.Y Siregar; Iman Supardan; Nono Sulistijarso (Jurnal Riset Kesehatan, 2015)
This Study aims to find out the effect of topical paste of daun sukun’s extract towards Fibroblast cell and Collagen tissues. These have important roles in Periodontitis healing’s process. This Study was laboratory experimental. The subjects were 12 Wistar mice which were made Periodontitis by injecting Aa bacteria 108 mg/ml on cervical 11 in three weeks. Devided into 2 groups, the first was given Sukun extracts topically and the second was given nothing. Serial decapitation on day 3,7,10 and 14 was administered on each group and their gingiva were examined with HE paint. The result showed paste of Sukun leaves extract impact signifficantly toward Fibroblast cell (Sig.0.032) but not on Collagen tissues (Sig. 0.837). The fibroblast cell were going up on the seventh day as well as the thickness of Collagen tissues. Periodontits healing is marked by the increase of fibroblast cell and the tickness of Collagen. It is suggested to make the product in gel.